2012
DOI: 10.1016/j.kjms.2012.02.015
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on illness perception and adherence among hypertensive patients

Abstract: Successful blood pressure (BP) control requires good adherence to medication and specific health-related behaviors. However, the BP control rate is not optimal, and limited research has focused on the patient's perspective. This study aimed at investigating the illness perceptions of hypertensive patients and how they relate to drug adherence. One hundred and seventeen hypertensive patients enrolled in this study, and data were collected in a family physician clinic of a medical center located in northern Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
4
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 24 publications
7
53
4
7
Order By: Relevance
“…Reasons for exclusion were: (a) not peer reviewed (5 studies); (b) not in English (2 studies); (c) study analysis did not include clustering methods (38 studies); (d) variables other than illness representation subscales were used to create groups (27 studies); (e) illness representation was not measured using the subscales of the IPQ‐R (change scores 6 studies, Brief IPQ 5 studies, other measures 6 studies, 17 studies total); (f) sample population did not have a chronic disease (2 studies); and (g) outcome variables were not health‐related. A total of 12 studies met inclusion criteria (Aujla, Walker, Sprigg, & Vedhara, 2018; Berry, Davies, & Dempster, 2017; Flora, Anderson, & Brawley, 2015; Graham, Rose, Hankins, Chalder, & Weinman, 2013; Harrison et al, 2014; Hobro, Weinman, & Hankins, 2004; Hsiao, Chang, & Chen, 2012; Lin & Heidrich, 2012; Lopes et al, 2018; McCorry et al, 2013; Norton et al, 2014; Turkington, Dempster, & Maguire, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Reasons for exclusion were: (a) not peer reviewed (5 studies); (b) not in English (2 studies); (c) study analysis did not include clustering methods (38 studies); (d) variables other than illness representation subscales were used to create groups (27 studies); (e) illness representation was not measured using the subscales of the IPQ‐R (change scores 6 studies, Brief IPQ 5 studies, other measures 6 studies, 17 studies total); (f) sample population did not have a chronic disease (2 studies); and (g) outcome variables were not health‐related. A total of 12 studies met inclusion criteria (Aujla, Walker, Sprigg, & Vedhara, 2018; Berry, Davies, & Dempster, 2017; Flora, Anderson, & Brawley, 2015; Graham, Rose, Hankins, Chalder, & Weinman, 2013; Harrison et al, 2014; Hobro, Weinman, & Hankins, 2004; Hsiao, Chang, & Chen, 2012; Lin & Heidrich, 2012; Lopes et al, 2018; McCorry et al, 2013; Norton et al, 2014; Turkington, Dempster, & Maguire, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…There is no similar systematic study using the Health Belief Model that has assessed attitudes toward drugs in nonpsychiatric patients taking medications for other chronic conditions. A few studies of patients' attitudes toward drugs have been conducted in epilepsy [46] and hypertension [47,48], but the only article that systematically applied the Health Belief Model is a review of the literature on drug attitudes toward statins, in which published studies are reinterpreted with the use of this model [49]. …”
Section: Limited Studies On the Attitudes Toward Medications In Medicmentioning
confidence: 99%
“…Adherence or orders and information compliance are influenced by patient's beliefs and their health conditions [7]. Some studies have shown negative attitudes of hypertensive patients toward their disease.…”
Section: Introductionmentioning
confidence: 99%